2012
DOI: 10.1158/1535-7163.mct-11-0750
|View full text |Cite
|
Sign up to set email alerts
|

TheEGFRT790M Mutation in Acquired Resistance to an Irreversible Second-Generation EGFR Inhibitor

Abstract: Molecular target therapies using first-generation, reversible epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKI), such as gefitinib or erlotinib, have been shown to be effective for patients with non-small cell lung cancer (NSCLC) who harbor activating mutations in EGFR. However, these patients eventually develop resistance to the reversible TKIs, and this has led to the development of second-generation, irreversible EGFR inhibitors. Currently, the mechanism of acquired resistance to irre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
108
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(109 citation statements)
references
References 35 publications
0
108
0
1
Order By: Relevance
“…These compounds are hindered by dose-limiting toxicities associated with EGFR WT inhibition, and therefore, cannot be adequately dosed to inhibit the T790M drug-resistant mutation. Moreover, these inhibitors do not prevent the emergence of the T790M drug-resistant mutation (8,33). Therefore, there is a clinical need for next generation inhibitors that can overcome the drug-resistant EGFR mutation while sparing wild-type EGFR, and thus, avoid or reduce the doselimiting toxicities that have restricted the therapeutic benefits of first-and second-generation EGFR inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds are hindered by dose-limiting toxicities associated with EGFR WT inhibition, and therefore, cannot be adequately dosed to inhibit the T790M drug-resistant mutation. Moreover, these inhibitors do not prevent the emergence of the T790M drug-resistant mutation (8,33). Therefore, there is a clinical need for next generation inhibitors that can overcome the drug-resistant EGFR mutation while sparing wild-type EGFR, and thus, avoid or reduce the doselimiting toxicities that have restricted the therapeutic benefits of first-and second-generation EGFR inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…However, wild-type EGFR and EGFR T790M mutant share highly similar three-dimensional structures and virtually identical binding affinities with ATP. Consequently, almost all of the reported, irreversible EGFR inhibitors displayed equal potencies against T790M mutant and wild-type enzyme, highlighting the current challenge in the search for EGFR T790M mutant-selective inhibitors [10,11]. WZ4002 (3) [12], rociletinib (4) [13], and osimertinib (5) [14,15] are typical EGFR T790M inhibitors and a phase trial has revealed capability in gefitinib-resistant NSCLC patients who suffer from EGFR mutations (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The threonine to methionine change at the 790 amino acid ''gatekeeper'' residue in the EGFR kinase domain has been shown to confer resistance by increasing the affinity for ATP, compromising the potency of reversible TKIs [5]. In these T790M-harboring cells, inhibition of EGFR by currently available second-generation EGFR-TKIs is still not sufficient to physiologically prevent the emergence of cells that are dependent on EGFR signaling [6]. For instance, afatinib (BIBW 2992, Boehringer Ingelheim GmbH), a panHER inhibitor of EGFR, HER2 and HER4 kinases, retains some activity in tumors with a T790M mutation.…”
Section: Introductionmentioning
confidence: 99%